Liver‐type fatty acid‐binding protein and neutrophil gelatinase‐associated lipocalin in cats with chronic kidney disease and hyperthyroidism - Thirawut Kongtasai (Wiley, 2021)
Abstract Background Liver‐type fatty acid‐binding protein (L‐FABP) and neutrophil gelatinase‐associated lipocalin (NGAL) are candidate biomarkers for the detection of early chronic kidney disease (CKD) in cats. Objective To evaluate urinary and serum L‐FABP and NGAL concentrations in CKD cats and in hyperthyroid cats before and after radioiodine (131I) treatment. Animals Nine CKD cats, 45 healthy cats and hyperthyroid cats at 3 time points including before (T0, n = 49), 1 month (T1, n = 49), and 11 to 29 months after (T2, n = 26) 131I treatment. Methods Cross‐sectional and longitudinal study. Serum L‐FABP (sL‐FABP), serum NGAL (sNGAL), urinary L‐FABP (uL‐FABP), and urinary NGAL (uNGAL) were compared between the 3 groups and between hyperthyroid cats before and after treatment. Data are reported as median (min‐max). Results CKD cats had significantly higher sL‐FABP (13.50 [3.40‐75.60] ng/ml) and uL‐FABP/Cr (4.90 [0.97‐2139.44] µg/g) than healthy cats (4.25 [1.34‐23.25] ng/ml; P = .01 and 0.46 [0.18‐9.13] µg/g; P < .001, respectively). Hyperthyroid cats at T0 had significantly higher uL‐FABP/Cr (0.94 [0.15‐896.00] µg/g) than healthy cats (P < .001), thereafter uL‐FABP/Cr significantly decreased at T2 (0.54 [0.10‐76.41] µg/g, P = .002). For the detection of CKD, uL‐FABP/Cr had 100% (95% confidence interval [CI], 66.4‐100.0) sensitivity and 93.2% (95% CI, 81.3‐98.6) specificity. There were no significant differences in sNGAL and uNGAL/Cr between the 3 groups. Conclusions and Clinical Importance L‐FABP, but not NGAL, is a potential biomarker for the detection of early CKD in cats. Utility of uL‐FABP to predict azotemia after treatment in hyperthyroid cats remains unknown.